ARP Case Report: Primary Adrenal Lymphoma - Manso,Nuno Lupi (2024)
Abstract Primary adrenal lymphoma is a rare and aggressive entity affecting mostly older males and that should be considered in the differential diagnosis of bilateral, hypovascular and hypermetabolic bulky adrenal masses.